The Role of Midwives in Women's Empowerment: A Narrative Review - Fahimeh Khorasani; Elnaz Iranifard; Robab Latifnejad Roudsari; Khadijeh Mirzaii Najmabadi (Mashhad University of Medical Sciences, 2023)
Background & aim: Midwives can participate in empowering women by improving women's health and supporting them through different life stages. Despite the emphasis on the role of midwives in empowering women, the strategies through which midwives can fulfill this role are not fully investigated. The aim of this study was to review the role of midwifes in women's empowerment.Methods: In this narrative review, which was conducted based on the Scale for Assessing Narrative Review Articles (SANRA), databases including ISI, Scopus, PubMed, Cochrane library, PsycInfo, SID, Magiran and IranMedex were searched by two researchers without time limit up to September 2022, using keywords of "female empowerment", "empowerment", "midwife", "midwifery" and their Persian equivalents. All the original articles focused on midwives' role in women's empowerment were included. Articles without access to full-text, conference papers, short communications and editorials were excluded. Qualitative synthesis was conducted on 27 articles included in the study.Results: Two main categories including "reproductive and sexual health" and "gender-based discrimination and violence" were identified. The first category included midwives' role in pregnancy, childbirth, postpartum, breastfeeding and family planning services. The second category involved midwives role to empower women in confronting domestic violence and harmful cultural practices.Conclusion: Despite midwives success in empowering women, they face many obstacles, both within and outside the health system, especially in combatting against discrimination and gender-based violence, which need to be addressed. To empower women, it is crucial that governments, communities and international organizations pay more attention to the role of midwives in women's empowerment.